What happens at two? Immunisation stakeholders' perspectives on factors influencing sub-optimal childhood vaccine uptake for toddlers in regional and remote Western Australia - Samantha J. Carlson; Sian Tomkinson; Adam Hannah; Katie Attwell (BMC, 2024)
Abstract Background In Western Australia (WA), children aged 24 months living regionally or remotely (non-urban) have suboptimal vaccine uptake. As there has not yet been a systematic approach to understanding the facilitators and barriers to childhood vaccination in regional and remote WA, this study aimed to understand the views of key immunisation stakeholders regarding barriers and solutions. Methods Drawing on the World Health Organization's "Tailoring Immunization Programmes" approach, we undertook a qualitative study with three forms of data collection: (1) semi-structured interviews with immunisation experts within Australia's immunisation system, (2) a semi-structured focus group with immunisation coordinators and health workers working in regional or remote WA, and (3) member checking with senior staff from WA Health. Data from the interviews and focus group was deductively analysed using the Capability-Opportunity-Motivation-Behaviour (COM-B) model on NVivo 20. Results There was no clear consensus on the typical under-vaccinated child in country WA. A range of barriers were identified: lack of awareness of the vaccine schedule, difficult access to vaccination services, a shortage in a workforce able to have meaningful conversations with vaccine hesitant parents, ineffective reminder systems, and the rapid spread of misinformation. Participants described previous efforts used to improve vaccine uptake, and felt the following would improve uptake: better access to vaccine clinics, building capacity of Aboriginal Health Workers, and vaccine reminders. Conclusion This is the first time the facilitators and barriers to routine childhood vaccine uptake in country WA has been explored. Addressing some of these barriers may see an increase in uptake.